Knowledge Flows in the Global Innovation System: Do U.S. Firms Share More Scientific Knowledge than their Japanese Rivals? - Spencer, Jennifer W. (Journal of International Business Studies, 2000)
In this paper, I test the common assumption that Japanese firms strive to appropriate knowledge from the global scientific community while sharing little in return. I found no support for this conventional perspective in the flat panel display industry. U.S. firms shared no more knowledge with their global scientific community than Japanese firms. Similarly, Japanese firms appropriated no more knowledge from the global community than their U.S. counterparts.